ChemInform Abstract: A Multidisciplinary Approach to Understand the Interactions of Nonthermal Plasma and Catalyst: A Review. Issue 40 (October 2015) - Kim, Hyun‐Ha; Teramoto, Yoshiyuki; Negishi, Nobuaki; Ogata, Atsushi
Abstract Review: 140 refs.